Cooking for health: a 4-week healthy menu guide -Book 3 - Abiva, Cris C.; Callanta, Luz S. ; Jamines, Atel E. (Pasig City, 2007)
A practical meal planning guide designed to help individuals and families adopt a healthier lifestyle through balanced, nutritious meals. It features a complete four-week menu plan with easy-to-follow recipes, portion guidance, and tips for preparing wholesome dishes that support overall wellness.
Keywords: Cookery, Philippine